2005
DOI: 10.1007/s00442-005-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of the evolution of increased competitive ability hypothesis in goldenrod, Solidago gigantea

Abstract: The mechanisms that allow introduced plants to become invasive are poorly understood. Here, we present a test of the evolution of increased competitive ability hypothesis, which holds that because specialized natural enemies may be absent from the introduced range, exotic plants may evolve to invest less in anti-herbivore defenses and thereby gain a competitive advantage over native plants. We grew Solidago gigantea plants derived from both the native range (North America) and the invasive range (Europe) in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 33 publications
6
73
4
Order By: Relevance
“…Plant height and inflorescence size, as morphological traits are directly connected with competitiveness and reproduction, and considered to be useful in assessing invasive potential of the species [53][54][55]. The results of our study show, that different Solidago species revealed different potential invasiveness expressed by morphological traits.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Plant height and inflorescence size, as morphological traits are directly connected with competitiveness and reproduction, and considered to be useful in assessing invasive potential of the species [53][54][55]. The results of our study show, that different Solidago species revealed different potential invasiveness expressed by morphological traits.…”
Section: Discussionmentioning
confidence: 50%
“…Additionally, S. graminifolia achieved its highest abundance on acidic soils [32]. On the other hand, results of this study show, that differences in the height of ramets and inflorescence size can be related to soil parameters and overshading by trees.Plant height and inflorescence size, as morphological traits are directly connected with competitiveness and reproduction, and considered to be useful in assessing invasive potential of the species [53][54][55]. The results of our study show, that different Solidago species revealed different potential invasiveness expressed by morphological traits.…”
mentioning
confidence: 50%
“…
Exotic plant species that spread into natural and seminatural plant communities are a serious threat to native species and affect the structure and dynamics of the vegetation [1]. The majority of invasive plant species are strong competitors that displace native species, decrease biodiversity, and alter ecosystem services [2][3].

Traditional grasslands in Europe include some of the most species-rich habitats and richest soil biodiversity.

…”
mentioning
confidence: 99%
“…The authors argued that this may increase the ability of S. gigantea to compete against established species in dense stands or nutrient-poor sites. Meyer et al (2005) tested the evolution of increased competitive ability hypothesis and found that European (introduced) S. gigantea are less resistant to American foliar pathogens and do not perform as well in the presence of insect herbivores as American (native) S. gigantea. Weber (2001) found evidence that strongly suggested that the spread of S. gigantea has not reached its limits and that its range expansion will continue.…”
Section: Mechanism Of Invasion and Ecosystem Attribute That Can Be Momentioning
confidence: 99%